2020
DOI: 10.21203/rs.3.rs-16932/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence variation of SARS-CoV-2 spike protein may facilitate stronger interaction with ACE2 promoting high infectivity

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease (COVID-19), is a novel beta coronavirus emerged in China in 2019. Coronavirus uses spike glycoprotein to interact with host angiotensin-converting enzyme 2 (ACE2) and ensure cell recognition. High infectivity of SARS-CoV-2 raises questions on spike-ACE2 binding affinity and its neutralization by anti-SARS-CoV monoclonal antibodies (mAbs). Here, we observed Val-to-Lys417 mutation in the receptor-binding domains (RBD) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
5
9
0
Order By: Relevance
“…Two amino acid stretches of 445-456 and 488-501 which participate in ACE2 binding, were truncated from the RBD and joined through flexible linker, LIGRGP, to optimally orient the joining peptides and retain its target-binding ability. In its resting (RBD down ) position, the same sheet-loop-sheet motif lays between the NTD and the RBD domains of the adjustment S protomer, as we have shown previously (30). Thus, in addition to ACE2-RBD hindrance, we suggest that CSNP4 can present RBD for the immune surveillance by limiting its spontaneous position switching.…”
Section: Design Of the Candidate Csnpssupporting
confidence: 75%
See 1 more Smart Citation
“…Two amino acid stretches of 445-456 and 488-501 which participate in ACE2 binding, were truncated from the RBD and joined through flexible linker, LIGRGP, to optimally orient the joining peptides and retain its target-binding ability. In its resting (RBD down ) position, the same sheet-loop-sheet motif lays between the NTD and the RBD domains of the adjustment S protomer, as we have shown previously (30). Thus, in addition to ACE2-RBD hindrance, we suggest that CSNP4 can present RBD for the immune surveillance by limiting its spontaneous position switching.…”
Section: Design Of the Candidate Csnpssupporting
confidence: 75%
“…In the current study, we attempted similar approaches to design structurally constrained peptides, which could address the above-mentioned paradoxes of the spontaneous RBD-conformation switching and the interaction of S1 with soluble and membrane bound ACE2. We and others have delineated the ACE2-RBD interface and identified key residues that contribute to the binding strength of ACE2-RBD (15,17,18,30). Point mutation analyses could confirm that some of these residues are vital to the ACE2-RBD interface (31).…”
Section: Introductionmentioning
confidence: 88%
“…The sequence conservation of S1 RBD yielded ≈73% identity, while the RBM region involved in direct interactions with the ACE2 receptor displayed a more significant variability as similarity between SARS-CoV and SARS-CoV-2 sequences dropped to ≈50% ( Figure 2 ). This analysis is fully consistent with previous studies [ 40 , 41 , 42 ] suggesting that a significant sequence variability of the SARS-CoV interacting residues from RBM motif may be accompanied by the corresponding local conformational changes. Structural studies confirmed these assertions revealing small but important changes in the RBM residues of SARS-CoV-RBD and SARS-CoV-2-RBD proteins [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultssupporting
confidence: 92%
“…It is suggested that this situation may be effective in the higher transmission rate of SARS-CoV-2 than SARS-CoV. In addition, the transformation of Pro-Ala475 and insertion of Gly482 into the AGSTPCNGV ring of RBD has prevented the neutralization of SARS-CoV-2 by anti-SARS-CoV mAbs 31 .…”
Section: Sars-cov-2 Mutationsmentioning
confidence: 99%